Barbados : 2009 Article IV Consultation; Staff Report; and Public Information Notice on its Consideration by the Executive Board. (IMF Staff Country Reports; Country Report ;, 2009)
Barbados has some of the highest social and competitiveness indicators in the region and enjoys investment-grade rating on its sovereign bonds. The staff report for Barbados's 2009 Article IV Consultation highlights economic developments and policies. Balance-of-payments pressures have increased, despite a narrowing in the current account deficit. In the absence of corrective measures, reserves are projected to decline to close to two months of imports over the medium term, which could lead to pressures on the currency peg.